Weed control in wheat (Triticum aestivum L.) under terai-agroecological region of West Bengal - Mukherjee, P K; Bhattacharya, P M; Chowdhury, A K (Journal of Cereal Research, 2011)
Wheat is an ecologically suitable crop in terai-agroecological region of West Bengal. High residual soil moisture in this region creates an opportunity for zero tilled wheat as late planting due to delay in harvesting of prceeding rice crop and aggressive growth of weeds (several species of Polygonum, Stellaria media Cyrill, and Oldenlandia diffusa L.) cause low productivity of conventional wheat. Considerable reduction of growth of dominant weed flora Polygonum persicaria L., P pensylvanicum L. and P orientale L. was recorded in zero tilled wheat, however, growth of other broadleaved weeds Stellaria media Cyrill, S aquatica Cyrill, Oldenlandia diffusa L., Vicia sativa L. and V hirsuta L. and grasses Cynodon dactylon (L) Pers., Setaria glauca (L.) Beauv and Digitaria sanguinalis (Retz.) Koel was increased considerably in succeeding years leading to gradual reduction of grain yield. Continuous application of 2,4-D caused shift in weed flora from several species of Polygonum to Physalis minina L. and Solanum nigram L. and aggressive growth of these weeds in succeeding years resulted in poor weed control efficiency, lower grain yield, lower values of net return and return cost ratio. Among the weed control treatments post-emergence application of carfentrazone ethyl @ 25 g ha-1 controlled the weeds (Physalis minima L., Solanum nigram L., Stellaria media Cyrill, S aquatica Cyrill, Oldenlandia diffusa L., Vicia sativa L.,V hirsuta L., several species of Polygonum, grasses and sedges) successfully resulting in highest grain yield and that, in turn, recorded highest net return. In comparison to conventional wheat more grain yield of 7.0 to 7.1 q ha-1 and more profit of Rs 10,490.00 to Rs 10,670.00 ha-1 were obtained in zero tilled wheat treated with glyphosate @ 1.5 kg ha-1 as pre-plant desiccators (stale seedbed) followed by post-emergence application of carfentrazone ethyl @ 25 g ha-1.